Distinct Response Inhibition Patterns in Obsessive Compulsive Disorder Patients and Pathological Gamblers - Kertzman, Semion G.; Poyurovski, Michael; Faragian, Sarit; Weizman, Ronit; Cohen, Koby; Aizer, Anat; Weizman, Abraham; Dannon, Pinhas N. (Frontiers in Psychiatry, 2018)
Abstract Background: Obsessive-compulsive disorder (OCD) and pathological gambling (PG) are common disorders. The cognitive models of OCD and PG focus on abnormalities in response inhibition. Although these functions have been studied in different PG and OCD samples, no study has compared the response inhibition in both. Methods: Medication-naïve OCD (n=61) and PG subjects (n=109) and healthy controls (n=131) performed CPT and Go/NoGo tasks. Results: Compared to healthy controls (HC), PG and OCD groups underperformed on speed and exhibited larger time variability on the CPT and Go/NoGo task. Only in OCD patients, a positive correlation between omission errors and response time (RT) was observed in the CPT. At the Go/NoGo task, a negative correlation between false alarms and RT (a fast-errors trade-off) was significant only in the PG group. The HC group had greater sensitivity values (d') than the OCD and PG groups in the Go/NoGo task. The PG group displayed lower d' values and more conservative response criterion in the CPT. In addition, only the OCD group expressed a high switching cost compared to both the PG and HC groups in terms of the RT and d' values. Conclusions: Both the PG and OCD groups demonstrated impaired response inhibition compared to the HC group. On several measures, the OCD and PG groups showed comparable impairments, and in others these were distinct. Thus, it appears that distinct neurocognitive patterns are involved in performance of the CPT and the Go/NoGo tasks among OCD and PG subjects whose cognitive status is currently under intensive investigation.